FRI0463 Optimizing the assessment of spondyloarthropathy among ophthalmologists –a regional survey. (15th June 2017) - Goel, S; Kumar, P; Moorthy, A
Abstract : Background: Spondyloarthropathy (SpA), is an under diagnosed clinical condition with an average delay in diagnosis of upto 8 years. The delay occurs due to non-specific symptoms which occur in young patients who are unlikely to present to healthcare services as well as presentations to different specialties as a result of extra-articular manifestations. 30% of Ankylosing Spondylitis (AS) patients have acute anterior uveitis (AAU) at some point due to the common link with HLA B-27. Uveitis may precede the diagnosis of Ankylosing Spondylitis (AS) by several years. Previous studies have shown that up to 40% (1) people with AAU have undiagnosed SpA, and are not routinely seen in rheumatology services due to lack of symptom and risk recognition. Early diagnosis in this group is essential to reduce the delay in diagnosis and improve the outcome of SpA. Objectives: 1.To identify the current assessment of inflammatory back pain, in patients with recurrent AAU, by local ophthalmologists. 2. To identify ways to improve cross specialty referral and reduce delay in the diagnosis of SpA. Methods: This is a prospective, questionnaire based semi qualitative study. The target population includes specialist ophthalmology trainees, consultants and GPs with a special interest in ophthalmology across the East Midlands. The questionnaire was piloted locally at a regional uveitis meeting. The improved questionnaire was then electronically communicated to ophthalmologists across East Midlands. The data was collated and analyzed using smartsurvey software. Results: We received 61 responses (response rate =51%), of which 57 (n=57) were analysed. The respondents largely comprised doctors working at university hospitals (74%) and consultants (45%) 17% of the respondents were not confident with taking an inflammatory back pain history. Of the remaining 83%, only 67% respondents would normally think to ask about the main symptoms of back pain related to AS. Thus 44% respondents were not competent in taking an inflammatory back pain history. With regards to their clinical practice, only 54% of respondents would routinely ask about symptoms of SpA in patients with recurrent AAU, even though 79% would test for HLA-B27. Furthermore, according to 42% of respondents they would never refer a recurrent AAU patient to a rheumatologist. Most respondents felt that work pressure was the most likely reason for deficit of proper SpA assessment and referrals, followed by lack of support by guidelines Conclusions: Our survey demonstrates a clear knowledge deficit among ophthalmologists regarding inflammatory back pain and the importance of assessing it in recurrent AAU patients. This can be improved by educating ophthalmologists about SpA in conferences and developing local guidelines about patients with HLA B-27 recurrent AAU related to assessment and referral. References: A novel evidence-based detection of undiagnosed spondyloarthritis in patients presenting with acute anterior uveitis: the DUET (Dublin Uveitis Evaluation Tool). Muhammad Haroon, Michael O'Rourke, Pathma Ramasamy, Conor C Murphy, Oliver FitzGerald. Acknowledgements: Respondents. Disclosure of Interest: None declared